CYBERCRIME VICTIM PROTECTION: LEGAL CHALLENGES AND STRATEGIES FOR MITIGATION - Iwan Rasiwan (Law Studies and Justice Journal (LAJU), 2025)
In today's digital era, cybercrime has increased significantly, posing major challenges to individuals and the legal system. Although much research focuses on technical and preventive aspects, legal protection for victims is still given little attention, creating gaps in access to justice. This research aims to identify and analyze the legal challenges faced by victims of cyber crime in obtaining justice and adequate protection. By using the approach Systematic Literature Review (SLR) and PRISMA guidelines, this research collects and analyzes articles peer-reviewed from Scopus, Web of Science and Springer databases. Data was analyzed thematically to identify patterns and key issues. Findings show that key challenges include disharmony in international regulations, jurisdictional issues, and limited victim protection in national laws. In addition, the lack of psychological support and the unpreparedness of law enforcement officers worsened the victim's condition. This research emphasizes the need for policy reform that is more responsive to the needs of cybercrime victims, as well as closer international collaboration to improve protection and access to justice. These findings contribute to the development of victimology theory and more inclusive legal practice.